An unpredicted side effect of bisphosphonates in a patient with chronic renal failure due to multiple myeloma: Reversible parkinsonism - (:unkn) unknown (My University, 2010)
In this report, we present a unique case in which the chemotherapeutic agent, i.e., zoledronic acid, deepened the hypocalcemia on the basis of chronic renal failure secondary to multiple myeloma and caused parkinsonism episodes. An 80-year-old female patient, who had been diagnosed as multiple myeloma and had been administered bisphosphonate therapy monthly for six months, was admitted to our emergency room with two parkinsonism episodes. Low serum calcium levels accompanied parkinsonism symptoms, which subsided with calcium replacement therapy in both episodes. Imaging did not reveal any pathology in the basal ganglia. The fact that the patient was cured both times with calcium replacement suggests that hypocalcemia was the actual cause. This can be interpreted as a unique case, reflecting the reversible functional impairment due to metabolic side effects of a chemotherapeutic agent rather than destructive changes in the basal ganglia.
Keywords: Drugs; Hypocalcemia; Parkinsonism disease; Secondary